Akibat Hukum Terhadap Harta Perkawinan Dalam Perjanjian Pranikah di Indonesia - Patrick Samky Radjah; Ni Made Jaya Senastri; I Made Aditya Mantara Putra (Jurnal Interpretasi Hukum, 2025)
Marriage is a legal relationship that helps create a happy household and family. Prenuptial agreements are essential for middle-class individuals as they protect the assets of both parties. However, the problem will become complicated when the couple divorces and has an impact on their property. The problem formulations raised are 1) How are the legal provisions of prenuptial agreements in Indonesian marriage law? and 2) What are the legal effects on marital property of prenuptial agreements? The research method used in this research is normative legal research using a statutory approach and conceptual approach. The results show that a prenuptial agreement must be made before marriage, as stated in Article 29 Paragraph (1) of the 1974 Marriage Law and Article 186 of the Civil Code. The legal implications of prenuptial agreements on marital property have changed after the issuance of the Constitutional Court Decision Number 69/PUU-XIII/2015 on March 21, 2016. This decision has an impact on the validity and legal consequences of marital agreements.